Ethical Dimensions of AI Within Cyber-Integrated Ecosystems - Radu SIMION (Studia Universitatis Babeș-Bolyai. Philosophia, 2025)
The innovative aspirations and territorial expansion ambitions of Homo technologicus have transformed it into a powerful entity capable of altering anthropic spaces and the surrounding environment in unprecedented ways. The consequences of advanced technologies and AI development can be vast, with asymmetric impacts and profound implications. Therefore, it is essential to examine potential concerns, vulnerabilities, threats, and promising advantages with transparency following the ethical values guiding the scientific community. In light of the rapid proliferation of new technologies, this article aims to examine the integration of artificial intelligence (AI) in waste management, focusing on its potential to enhance sustainable living and support biodiversity. To mitigate associated risks, the article proposes a holistic framework emphasizing relational ethics, ensuring transparency, accountability, and genuine ethical commitments in AI deployment. Additionally, the concept of humanwashing, where AI-enabled machines are anthropomorphized to foster acceptance and trust, raises concerns about misleading perceptions regarding AI capabilities. To effectively navigate these ethical challenges, the article advocates for a multidisciplinary approach involving researchers, policymakers, industry leaders, and civil society. Emphasizing relational ethics requires a shift from a traditional ethical framework to one that recognizes all actors' interconnectedness and cumulative impact. Ultimately, the article underscores the necessity of a rigorous ethical framework for integrating AI into waste management. This framework ensures that artificial intelligence technologies contribute positively to sustainable living, preserve biodiversity, and encourage a balanced interplay between people and technological advancements.